ОЛИЙ ТАЪЛИМ ТИЗИМИДА БЎЛАЖАК МУСИҚА ФАНИ ЎҚИТУВЧИЛАРИНИНГ КРЕАТИВ ТАЪЛИМИНИ ТАШКИЛ ЭТИШНИНГ ПЕДАГОГИК ИМКОНИЯТЛАРИ - Кенжебаева, С.С. (SCIENCE and SOCIETY, 2019)
The article outlines the pedagogical possibilities of organizing the creative education of future music teachers in the system of higher education based on scientific and theoretical sources. In the article the author also analyzes the content, forms and methods of organizing the creative education of future music teachers. The article gives a clear picture of the essence of the concept of creativity from the point of view of theoretical and practical understanding. In the higher education system, the possibility of using creative products to organizing creative education of future music teachers based on scientific approaches was analyzed.